Palladium‐Catalyzed Selective meta‐C−H Deuteration of Arenes: Reaction Design and Applications. Issue 40 (9th May 2019) - Bag, Sukdev; Petzold, Martin; Sur, Aishanee; Bhowmick, Suman; Werz, Daniel B.; Maiti, Debabrata
Abstract: Deuterium‐labeled compounds find wide applications in kinetic studies, and within the pharmaceutical industry. An easily removable pyrimidine‐based auxiliary has been employed for the meta ‐C−H deuteration of arenes. The scope of this Pd‐catalyzed deuteration using commercially available [D1 ]‐ and [D4 ]‐acetic acid has been demonstrated by its application in phenylacetic acid and phenylmethanesulfonate derivatives. A detailed mechanistic study led us to explore the reversibility of the non‐rate determining C−H activation step. The present study of meta ‐deuterium incorporation illustrates the template morphology in terms of selectivity. The applicability of this method has been demonstrated by the selective deuterium incorporation into various pharmaceuticals. Abstract : Only a slight change : A Pd‐catalyzed approach to meta ‐selective deuterium incorporation into arenes is reported. The Pd‐catalyzed proton–deuterium exchange using a pyrimidine‐based directing group method exploits the reversibility of the C−H activation step. A broad substrate scope including meta ‐deuterated pharmaceuticals is shown.